PENGARUH REPUTASI KAP DAN OPINI AUDIT TAHUN SEBELUMNYA TERHADAP OPINI AUDIT GOING CONCERN DENGAN FINANCIAL DISTRESS SEBAGAI MODERASI (STUDI EMPIRIS DILAKUKAN PADA PERUSAHAAN SEKTOR PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2022) - Bartinius, Putri Pelecia; Purwasih, Desy (Jurnal Nusa Akuntansi, 2024)
This study aims to analyze and provide empirical evidence of the influence of KAP reputation and previous year's audit opinion on going concern audit opinion with financial distress as a moderating variable. The type of research used is a quantitative approach with associative methods. The population in this research are property and real estate companies listed on the Indonesia Stock Exchange (BEI) in 2018-2022. The sampling technique in this research was purposive sampling and obtained research samples of 34 companies with observations for 5 years, a total of 170 research samples were obtained. The data analysis technique used is logistic regression using E-views version 9 software. Based on the results of the analysis, it is known that the KAP's reputation and the previous year's audit opinion simultaneously influence the going concern audit opinion. Partially, KAP's reputation has no effect on going concern audit opinion, while the previous year's audit opinion has an effect on going concern audit opinion. The results of logistic regression analysis (MRA) show that financial distress cannot moderate KAP reputation and the previous year's audit opinion on going concern audit opinion.